The Role of Qur'anic Interpretation in Islamic Legal Reasoning - Saleh, Fauzi (South East Asia Regional Intellectual Forum of Qoran Hadith (SEARFIQH), 2024)
Qur’anic interpretation has often been overlooked as a crucial element in the development of Islamic law, despite its undeniable connection to the juridical aspects of fiqh and qanun. This article examines the role of Qur’anic interpretation in deriving Islamic legal rulings, the prerequisites for producing valid fiqh-based interpretations, and its primary sources. This qualitative research employs documentation as its data collection technique, supported by a linguistic approach. The findings reveal three main points. First, interpretation (tafsir) serves as an idhah (explainer), bayan (clarifier), and kasyf (explorer) of legal verses. Second, valid interpretations require linguistic foundations, intertextual correlations (munasabat), historical contexts such as asbab al-nuzul, relevance to contemporary issues (fiqh al-waqi’), and a balanced understanding of illat (causal reasoning) and hikmah (wisdom). Furthermore, interpretation must adhere to appropriate frameworks and methodologies. Third, the sources of Qur’anic interpretation, in order of priority, include tafsir bi al-Qur'an, al-sunnah, the companions (sahabah), and the People of the Book, collectively termed tafsir bi al-ma’tsur. Meanwhile, interpretive efforts based on reasoning (tafsir al-ra’y), when aligned with scientific principles, are also considered valid.